Short-term outcomes of adjustable single-incision sling (Ajust™) procedure for stress urinary incontinence: a prospective single-center study. (March 2015) - Jiang, Tao; Xia, Zhijun; Cheng, Dali; Song, Yue; Guo, Zhiqiang; Hu, Qing; Zhao, Ying; Yin, Yitong
Abstract: Objectives: Slings have become the most widely performed surgical procedure for stress urinary incontinence (SUI) in last two decades. As the third generation sling, the efficacy of the early single-incision mini-sling was controversial. The aim of this study was to determine whether the new adjustable single-incision sling (Ajust™) is safe and effective in management of female SUI at 6–18 months follow-up. Study design: 69 patients with SUI according the inclusion and exclusion criteria were considered adjustable single-incision sling (Ajust™) from September 2012 to September 2013. 67 patients finished 6–18 months follow-up. The data about clinical parameter, operation, complication, Urogenital Distress Inventory-Short Form (UDI-6), Incontinence Impact Questionnaire-Short Form (IIQ-7) and International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) in Chinese were collected in preoperative, 6-month and 12-month follow-up. Results: All patients underwent successful adjustable single-incision sling (Ajust TM ) placement. The subjective cure rate and objective cure rate was 82.0%, 92.5% in 6-month follow-up and 82.3%, 91.2% in 12-month follow-up respectively. There were no significant perioperative complications such as bladder perforation, major bleeding requiring blood transfusion in the present study. Sling exposure was observed in two patients (3.2%). Conclusions: Adjustable single-incision sling (Ajust TM ) was a safe and effective option for treating female SUI and was associated with comparable subjective and objective success rates when compared to standard midurethral slings (TVT-O) at a 6–18 months follow-up.